Nature connectedness: an investigation into alleviating emotional disturbances among university students - Ahmad, Noorlila; Abd Rahman, Siti Fatimah; Syed Mahmood, Syarifah Rohaniah; Abdul Rashid, Khadijah Khalilah (Research and Scientific Innovation Society, 2024)
Emotional disturbances among undergraduate students have proven to affect students’ learning performance physically, emotionally and mentally. Among non-clinical treatments or techniques identified to address emotional disturbances is exposure to nature. This study investigates the impact of nature connectedness on emotional disturbances among 390 undergraduate students from various disciplines at one of Malaysia’s largest public universities. The research explores causal relationships and mediating effects among nature connectedness, restorativeness, spiritual values, and emotional disturbances, specifically stress, anxiety, and depression. The findings reveal significant associations between nature connectedness and restorativeness, as well as between nature connectedness and spiritual values. Notably, restorativeness emerges as a mediator between nature connectedness and stress, while spiritual values act as a mediator between nature connectedness and depression. The study underscores the potential of combining nature exposure and spirituality as a means of fostering psychological and emotional recovery. It is important to note that the generalizability of these findings is limited to the specific university sample in Malaysia. Nonetheless, the results contribute valuable insights into non-clinical interventions for addressing emotional challenges among undergraduate students.